The Implementation of Total Quality Management Based Online Learning at Educational Institutions - Ngatiman, Ngatiman; Supriyoko, Ki; Mulyo, Mufrod Teguh (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study uses a qualitative descriptive approach that describes thoroughly Total Quality Management in the implementation of online learning development in educational institutions. It reveals that the function of TQM in increasing the satisfaction of all users is very necessary and plays a role in providing better service. The role of the institution as a public educational institution does not only to provide educational facilities and infrastructure but standard operating procedures and quality control for learning must also exist and must be carried out by all users. In this case, users in learning are not only students but also lecturers, administrators, and assessors who also play important roles and contribute during the learning and teaching process.